Micro-computed tomography measurement of the marginal gap of different types of glass-ceramic veneers fabricated by heat-pressed technique. - Soma Qadir; Bassam Karem Amin (Erbil Dental Journal)
Background and Objective: This study was conducted to measure the marginal gap size of two different glass-ceramics fabricated by heat-pressed technique with micro-computed tomography scanning and analysis. Methods: Twenty sound human maxillary central incisors were prepared in window preparation design for the fabrication of laminate veneers. The samples were divided into two equal groups of Ten for each group. The impression for all the samples of each group was made by a conventional one-step impression technique using ImpregumTM Penta medium-bodied polyether impression material. The auto-mixing unit (pentamix) was used to ensure a standardized mixture for all the samples. Laminate veneers were fabricated using a heatpressed method with two different types of glass-ceramics ( IPS Emax press and Empress esthetic, Ivoclar Vivadent). IPS Emax ceramic was used for restorations of the first group, and IPS Empress esthetic was used for restorations of the second group. The finished restorations were cleaned and polished to be prepared for cementation. All of the restorations of each group were separately bonded to the samples of the corresponding groups using a light-cured cement. A dental surveyor with a fixed weight of 200g for standardization was used during the procedure. After the completion of the cementation procedure, the samples were cleaned and polished to be ready for a quantitative micro-computed tomography scanning and analysis for marginal gap size measurement. Results: The mean(±SD) value of IPS Emax was 0.056(±0.023)mm3, and the same value for IPS Empress was 0.128(±0.195)mm3. No statistically significant difference was found between in marginal gap size of both types of the glass-ceramic (p = 0.261). Conclusion: Within the limitations of this study, both IPS Emax and IPS Empress have comparable marginal accuracy.